Association of genetic polymorphisms of Calpain and Calpastatin genes with growth traits in Bandur sheep - KUMAR, S NAVEEN; JAYASHANKAR, M R; CHANDRASHEKHAR, M; PANDITH, VAGEESH; NAGARAJA, R; MANJU, G U (The Indian Journal of Animal Sciences, 2016)
The study was undertaken to determine genetic polymorphisms of Calpain and Calpastatin genes and to study their association with growth traits (birth weight, weaning weight, 6-month body weight and ADG) in Bandur ram lambs (100) distributed over core area of the home tract as well as from Livestock Research and Information Centre (Sheep), KVAFSU, Nagamangala. Miller’s high salt method was used for isolation of genomic DNA from venous blood. A 192 bp of CAPN (exons 5 and 6) and 620 bp of CAST (exons 1C/1D) genes were amplified by PCR using published primers. The PCR-SSCP analysis of CAPN gene revealed genotype frequency for AA (0.672) and AB (0.295) and allele frequency for A (0.820) and B (0.180), respectively. Alignment of A and B allele of Calpain by CLC Main Workbench 6.8.1 showed addition/insertion of one nucleotide ‘A’ in B allele. The PCR-RFLP analysis of CAST gene revealed frequency for genotypes MM (0.24), MN (0.59) and NN (0.17), and for alleles M (0.535) and N (0.465), respectively. The Chi-square test indicated that the studied population was in Hardy-Weinberg equilibrium. Five SNPs were identified in the intron between exon 1C and 1D of CAST. The association of CAPN and CAST genotypes with growth traits was analysed by ANOVA using GLM procedures of SAS 9.3. No significant associations were observed between polymorphisms of CAPN and CAST loci and growth traits.